2018
DOI: 10.1016/j.jvs.2017.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of endovascular aneurysm sealing from the multicenter Italian Research on Nellix Endoprosthesis (IRENE) study

Abstract: The preliminary results of this real-world multicenter study showed that EVAS with Nellix for the management of AAAs appears feasible. This device platform is associated with acceptable procedure-related mortality and low overall complication and reintervention rates. Definitive conclusions on the value of this novel device await long-term follow-up data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…The overall 8.9% mortality in this study is in accord with previous research (0.7%–9.5% 8 , 11 17 ) despite a longer follow-up. One patient died due to multiorgan failure after undergoing a conversion to open repair for an aortoenteric fistula, which is an interesting complication of EVAS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The overall 8.9% mortality in this study is in accord with previous research (0.7%–9.5% 8 , 11 17 ) despite a longer follow-up. One patient died due to multiorgan failure after undergoing a conversion to open repair for an aortoenteric fistula, which is an interesting complication of EVAS.…”
Section: Discussionsupporting
confidence: 92%
“… 8 The EVAS device consists of dual balloon-expandable stent-grafts surrounded by endobags that are filled in situ with polymer to achieve seal and anatomical fixation. 9 , 10 Since its launch in 2013, the Nellix device has shown a high aneurysm exclusion rate and a low frequency of complications, 8 , 11 17 but concerns exist as regards migration and endoleak in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…9 Consistently with these data, the Italian IRENE retrospective observational study reported a freedom from aneurysm-related reintervention of 98.3% at 1 month and of 94.7% at 12 months of follow-up; the rates of early and late type IA endoleak were 0.3% and 1.4%, respectively and the reintervention incidence was 3.7%, that included 1.4% of surgical open conversions. 10 Although the low reported incidence of type 1A endoleak after Nellix EVAS, these endoleaks are one of the major concerns of EVAS because they are mostly high-pressure leaks and may lead to late rupture of aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Early results appear to be promising but the ultimate role and value of this system are yet to be proven. 100,101 While a cut down is commonly required for the insertion of an endograft via the CFA, the feasibility of percutaneous EVAR has been reported with acceptable outcomes. 102 However, wound complication is a rare occurrence during EVAR.…”
Section: Infrarenal Abdominal Aortic Aneurysmmentioning
confidence: 99%